Analysis of The Implementation of Library Automation Systems Using SLIMS 9. - Saputra, Ahmad Marta Julianto; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research examines how the Diplomacy Library Automation of the Ministry of Foreign Affairs is implemented. This research aims to find out how the library automation system is implemented using Slims 9 in the Diplomacy library and to find out what obstacles librarians face in implementing the library automation system and how to overcome them. This research uses qualitative methods with observation, interviews and documentation. This research involved interviews with librarians at the Ministry of Foreign Affairs' Diplomacy library. The results of data analysis obtained during the research show that the use of the Senayan Library Management System (SLiMS) in the Diplomacy library of the Ministry of Foreign Affairs has fulfilled aspects of the Technology Acceptance Model (TAM) theory. SLiMS is considered useful for helping work in libraries, including assisting users in the process of searching for information. From this research, it is also known that the obstacles that are often experienced in processing SLiMS are that the internet network often disappears or is less stable, which can hinder the importing or searching process and also requires a long process to automate